Determinants of luxury counterfeit products in Pakistan - Tariq, Jalees (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The purpose of this thesis is to develop a holistic model to understand Pakistan consumers’ attitude towards counterfeit luxury products. The model is based on the Theory of Reasoned Action and Theory of Planned Behavior. The model consists of five personal antecedent, four social antecedents, and four additional variables including idealism, relativism, religiosity and ethics. Convenient sampling technique was used in this thesis for allocating samples to major cities of Pakistan. Mall intercept method was adopted for administering the questionnaire. The final sample size was 907. Although the constructs used in the thesis had established reliability and validity, but they were re-ascertained in the case of Pakistani respondents. Subsequently, exploratory factor analysis and confirmatory factor analysis of all the constructs individually, for all the exogenous models and overall model were ascertained. The reliability and validity of the final constructs were reassessed prior to testing the derived hypotheses through simple and multiple regression analyses.